(untitled) (International Journal of Medicine and Medical Sciences, 2011)
Background: Information on relationship between some biomarkers (uric acid and plasma fibrinogen) to the risk of myocardial infarction in patients with the metabolic syndrome among Africans is inexistent or scanty at best. Moreover there is a burden of myocardial infarction and metabolic syndrome on the population. Aims: The objective of this study was to establish the correlation: plasma fibrinogen and uric acid to myocardial infarction risks in patients with the metabolic syndrome. Method— A total 68subjects(34 patients and 34 healthy controls) aged between 18 -80 years were recruited for this study between November 2010 and March 2011.Patients for the study as well as the controls were recruited from Douala and were matched for sex ,age and place of residence. Trained nurses, using standard procedures, obtained blood pressure and anthropometric measurements and collected a venous blood sample for assay of plasma fibrinogen and uric acid. Serum uric acid was measured enzymatically after hydrolyzation to glycerol, Plasma glucose concentration was measured using an enzymatic reaction. Plasma fibrinogen was estimated by the Hook’s procedure. Data were analyzed using SPSS version 15 .. Results: Negative correlations were record between plasma fibrinogen and FBS, height, pulse, WHR and systolic pressure .Uric acid did not show any negative correlation with any of the indicators. There was no correlation between uric acid and fibrinogen (r=-0.056; p=0.599). As for uric acid, it showed very strong correlation with weight, height, waist circumference, diastolic pressure and body mass index.) Plasma fibrinogen showed the strongest correlation with Hip circumference (r=0.362, p<0.001)) while with the waist circumference showed a relatively weaker though significant correlation (r=0.240, p=0.023) Plasma fibrinogen did not show any significant difference between patients group and control groups and did not show any significant correlation with the determinants of the metabolic syndrome Conclusions: Uric acid and not plasma fibrinogen may be considered as a component of the metabolic syndrome. Further investigation is necessary to confirm the results of this preliminary study.